Bacillus antri sp. nov., isolated from cave soil. Issue 8 (24th May 2019) - Rao, Manik Prabhu Narsing; Dong, Zhou-Yan; Zhang, Hui; Niu, Xue-Ke; Zhang, Kun; Fang, Bao-Zhu; Xiao, Min; Kang, Ying-Qian; Li, Wen-Jun
Abstract : A Gram-stain-positive, strictly aerobic, rod-shaped, motile, endospore-forming strain, SYSU K30001 T, was isolated from a soil sample collected from a cave in Xingyi county, Guizhou province, south-west China. Phylogenetic analysis based on 16S rRNA gene sequences indicated that strain SYSU K30001 T belonged to the genus Bacillus, with the highest sequence similarity to the type strain of Bacillus panaciterrae (98.1 %). Growth occurred at pH 6.0–9.0 (optimum, pH 7.0), at 28–55 °C (optimum, 28 °C) and in the presence of 0–3 % (w/v) NaCl (optimum in the absence of NaCl). Strain SYSU K30001 T contained meso -2, 6-diaminopimelic acid in the cell-wall peptidoglycan and MK-7 as the only isoprenoid quinone present. The polar lipids consisted of diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine and an unidentified glycolipid. The major fatty acids were iso-C15 : 0, iso-C17 : 1 ω 10 c, anteiso-C14 : 0 and iso-C17 : 0 . The genome G+C content was 39.8 mol%. The average nucleotide identity values between SYSU K30001 T and B. panaciterrae DSM 19096 T were 72.1 % (ANIb) and 83.1 % (ANIm), which were below the cut-off level (95–96 %) for species delineation. Based on phenotypic, chemotaxonomic and molecular characterizations, strain SYSU K30001 T represents a novel species of the genus Bacillus, for which the name Bacillus antri sp. nov. is proposed. The type strain is SYSU K30001 T (=KCTC 33954 T =CGMCC 1.13871 T ).